2006
DOI: 10.1002/oti.219
|View full text |Cite
|
Sign up to set email alerts
|

Coping with chronic pain associated with cerebral palsy

Abstract: Fifty-nine adults with cerebral palsy (CP) were administered, via inperson interviews, measures of pain intensity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 16 publications
5
32
1
1
Order By: Relevance
“…Our findings suggest that the treatment of patients with WAD of a short duration should be more focussed on modifying catastrophising thoughts than on developing certain pain coping strategies, because it is a more effective way of reducing levels of disability and depression in a short time after the accident. Other researchers have also pointed out the need to pay attention to reducing catastrophising in the treatment of chronic pain problems [19,[52][53][54]. In the whiplash field, a recent study [55] also highlighted the utility of a psychosocial intervention that addresses pain catastrophising in a sample of patients with chronic WAD.…”
Section: Discussionmentioning
confidence: 95%
“…Our findings suggest that the treatment of patients with WAD of a short duration should be more focussed on modifying catastrophising thoughts than on developing certain pain coping strategies, because it is a more effective way of reducing levels of disability and depression in a short time after the accident. Other researchers have also pointed out the need to pay attention to reducing catastrophising in the treatment of chronic pain problems [19,[52][53][54]. In the whiplash field, a recent study [55] also highlighted the utility of a psychosocial intervention that addresses pain catastrophising in a sample of patients with chronic WAD.…”
Section: Discussionmentioning
confidence: 95%
“…Reduction of activity, through resting or avoidance, has been associated with positively associated with pain interference in people with cerebral palsy and muscular dystrophy, and with symptoms of depression in people with cerebral palsy (Engel, et al, 2000;Miro, et al, 2009). Seeking social support has been found to be positively associated with pain-related disability among people with cerebral palsy and muscular dystrophy (Engel, et al, 2006;Miro, et al, 2009), a finding that may initially appear counter-intuitive. The authors of the cerebral palsy study identified the fact that the items on the scale potentially reflect both adaptive and maladaptive aspects of social support seeking (Engel, et al, 2006).…”
Section: Behavioural Responses To Painmentioning
confidence: 99%
“…Seeking social support has been found to be positively associated with pain-related disability among people with cerebral palsy and muscular dystrophy (Engel, et al, 2006;Miro, et al, 2009), a finding that may initially appear counter-intuitive. The authors of the cerebral palsy study identified the fact that the items on the scale potentially reflect both adaptive and maladaptive aspects of social support seeking (Engel, et al, 2006). However, operant models of chronic pain suggest that pain contingent social support would result in increased disability, which may also provide a parsimonious explanation of the findings.…”
Section: Behavioural Responses To Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain limits activity (Turk et al, 1997), and two-thirds can anticipate having moderate to severe, 24% constant, and 56% daily pain. In another study 32% reported dissatisfaction with pain management (Engel et al, 2006). Other causes of chronic pain in musculoskeletal disorders include hip dysplasia (Hodgkinson et al, 2001) leading to postural problems and back pain.…”
Section: Medical Complications Of Cerebral Palsy In Adulthoodmentioning
confidence: 97%